RNA methyltransferase NSUN2-mediated m5C methylation promotes Cr(VI)-induced malignant transformation and lung cancer by accelerating metabolism reprogramming - Rui-Ke Zhang; Yan Li; Fan-Li Sun; Zhi-Hao Zhou; Yun-Xia Xie; Wen-Jing Liu; Wei Wang; Jian-Ge Qiu; Bing-Hua Jiang; Lin Wang (Environment International)
Hexavalent chromium [Cr(VI)], one common environmental contaminant, has long been recognized as a carcinogen associated with lung cancer, but roles and mechanisms of Cr(VI)-induced epigenetic dysregulations in carcinogenesis remain to be investigated. In this study, we identified that RNA m5C methyltransferase NSUN2 was significantly upregulated in Cr(VI)-transformed cells and lung tissues of Cr(VI)-exposed mice. Inhibition of NSUN2 reduced cell proliferation, migration, colony formation and tube formation abilities. We found NSUN2-mediated m5C modification induced metabolic reprogramming and cell cycle by promoting the mRNA stabilities of ME1, GLUT3 and CDK2. In addition, knockdown of NSUN2 attenuated tumorigenesis and angiogenesis in vivo. RNA m5C reader ALYREF was identified to be involved in NSUN2-mediated m5C modification in Cr (VI)-induced carcinogenesis. Further study showed that EP300 induced NSUN2 upregulation through transcriptional activation by inducing histone modification at H3K27ac site for regulating Cr(VI) carcinogenesis. Our findings demonstrated novel role and mechanism of NSUN2 and epigenetic changes by increasing the RNA m5C modification that are important for Cr (VI)-induced carcinogenesis through NSUN2/ALYREF pathway. NSUN2, ALYREF, ME1, GLUT3 or/and CDK2 may be used as potential new biomarkers or/and therapeutic target(s) in the future.